(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Scientific understanding of speech culture in this article- scientific views of linguists, Methodist scientists and psychologists on theoretical justification, content of the development of speech culture in future educators and psychologists, the culture of speech, the formation of practical skills for mastering literary language norms (pronunciation, spelling and grammar), the expansion of knowledge about speech styles,the cultivation of oral and written forms of speech, a communicative approach,the improvement of normative, ethical and communicative levels.